Peningkatan Kompetensi Materi Fluida Statis Melalui Model Pembelajaran Eksperimen Inkuiri Terbimbing Pada Peserta Didik Kelas X TPEM 2 SMK Negeri 1 Kedungwuni Kabupaten Pekalongan Semester Genap Tahun Pelajaran 2014/2015 - Fatwa, Nur (Jurnal Profesi Keguruan, 2015)
The problem of this research was how the students active participation and competence static fluid material for the students of class X TPEM 2 SMK Negeri 1 Kedungwuni Kabupaten Pekalongan in the second semester academic year 2014/2015 using the guided inquiry experiment learning model. This research was carried out in two cycles, each cycle was conducted in three meetings. The research shows that the students competence increased from 72,59 in cycle I to 85,22 in cycle II. It also proves that the students active participation improved.within the two cycles.